Commitment and Wellbeing: The Relationship Dilemma in a Two-Wave Study - Chambel, Maria José; Carvalho, Vânia Sofia (Frontiers in Psychology, 2022)
There has been little consensus around the sequential relationship between organizational affective commitment and workers’ well-being. In line with the Conservation of Resources Theory, results of this two-wave study with a contact center employee sample (N = 483) showed that organizational affective commitment decreases work ill-being (i.e. burnout) and increases work well-being (i.e. work-engagement). Furthermore, in keeping with the loss spiral assumption of this theory, the mediating role of burnout in the affective commitment-health relationship is supported in this study. However, in accordance with the Job Demand-Resources, work engagement was found not to prevent effects on health. The findings have implications for the organizational affective commitment theory, as well as for organizational occupational health policies and interventions.